PARENT INVOLVEMENT AND ACADEMIC ACHIEVEMENTS OF PRIMARY SCHOOL CHILDREN IN KOLE NORTH COUNTY, KOLE DISTRICT, UGANDA: A CROSS-SECTIONAL STUDY - Silvestor Ogwal; Edmand Bakashaba; Edirisa Ntale (Student's Journal of Health Research, 2023)
Background The purpose of the study was to examine the relationship between parent involvement and academic achievements of primary pupils in Kole North County, Kole District.  Methodology The study was a descriptive, correlational, and cross-sectional survey research design. Further, it was both quantitative and qualitative. The study used 32 head teachers of primary schools in Kole North County, Kole District as the respondents of this study. Results The findings revealed that 87% of the respondents were males and 13% of the respondents were females. Also, 59.4% of the respondents were aged 41-50 years, 28.1% of the respondents were aged 51-60 years and 12.5% of the respondents were aged 31- 40 years. The correlation between parents' discussions with pupils and their academic performance in a secondary school within Kole North County was 0.843 with a sig value of 0.001. The correlation between parents' attendance of school programs and completion of primary education by primary pupils was 0.411 with a sig. value of 0.018. This indicates a positive significant relationship between parents' attendance of school programs and completion of primary education by primary pupils in North Kole County. Conclusions The education level of parents and parents' involvement in providing scholastic materials and attending school programs contributes to the academic achievements of their children in Kole North County. Recommendations Parents should strive hard to provide school requirements in time to avoid sending students home as well as lack of scholastic materials. Parents should also do extra coaching of the children using a private tutor to help their children excel with better grades.